Effects of the COVID-19 induced cotton crisis on agricultural production and livelihoods of smallholders in southern Mali - Dissa, Arouna; Slingerland, Maja; Giller, Ken E.; Descheemaeker, Katrien (Frontiers in Sustainable Food Systems, 2024)
Smallholder farming systems are vulnerable to disruptions. The COVID-19 pandemic weakened the financial ability of the Malian government in the 2020-21 growing season to subsidize cotton farmers’ access to mineral fertilizers and the cotton company (CMDT) could not offer a good cotton price. Consequently, farmers refused to grow cotton, leading to a cotton crisis with implications on crop production and farmers’ livelihoods. We used data collected over three consecutive growing seasons in the old cotton basin of Koutiala and analysed them using two-way mixed ANOVA over selected indicators related to farm and household components. The analysis was done for farms of different resource endowment, through comparing the cotton crisis season to the two previous normal seasons. Besides the abandonment of cotton, the total cropped area and area devoted to maize reduced in 2020-21, while the area allocated to millet, sorghum and cowpea increased, especially for cotton farmers with medium and high resource endowments. In addition, the nitrogen use intensity dropped at the farm level and particularly for the cereal crops, but without negative effect on yields of maize, millet and sorghum. Food self-sufficiency and income per capita significantly increased for the medium resource farms, while income dropped for the high resource farms with large herds. The farming system was able to absorb the shock of limited access to fertilizer for one season, due to the elimination of otherwise strong labour competition between cotton and cereal crops, favourable weather conditions and farmers’ responsive coping with the cotton crisis. This study revealed the importance of disaggregated livelihood evaluations, because resource endowments have implications not only for the actual effect on livelihoods, but also for farmers’ adaptive capacity.